God grew tired of us - Pace, Molly Bradford; Quinn, Christopher; Walker, Tommy; Kidman, Nicole, 1967-; Bior, Panther; Dau, John Bul.; Pach, Daniel Abol.; Saft, Jamie; Newmarket Films; Silver Nitrate (Firm); National Geographic Films; Lost Boys of Sudan, Inc.; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2007)
Presents the plight of young, male Sudanese refugees, known as "lost boys," being displaced to foreign countries due to civil war in their homeland. The film tells the story of three of the lost boys who struggled to come to the United States for a better life, while still attempting to assist the family and friends they have left behind.
Special featues: Anamorphic widescreen verion -- Commentary with director and Lost Boys -- Finding the Lost Boys -- Language: English 5.1 Dolby digital -- Subtitles: English, Spanish.
DVD, region 1; Dolby digital.
In English, with optional English or Spanish subtitles.
Closed captioned.
MPAA rating: PG; thematic elements and some disturbing images.
Narrator, Nicole Kidman.
Featuring, Panther Bior, John Bul Dau, Daniel Abol Pach.
Keywords: Sudan -- History -- Civil War, 1983-2005.; Sudan -- Politics and government -- 1985-; Refugees -- Sudan; Refugees -- United States; Cine Americano; Video recordings for the hearing impaired; Documentary films; Nonfiction films; Feature films